TAPUNG PADA MASA KERAJAAN SIAK TAHUN 1915-1946. - Wahyuningsih, Sri; ', Isjoni; Oemar, Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Historiography is to reconstruct past events in a systematic and objective manner to collect, evaluate, verify, and synthesizes the evidence to establish the facts and obtain robust conclusions. The name of Tapung taken from the name of a river that crosses an area and the area was named Tapung as we know today. The purpose of this research is 1) To know the history of Tapung during the Kingdom of Siak 2) To know the history of Tapung during the Dutch colonization 3) To know the history of Tapung on the Japanese colonization 4) To know the history of Tapung during the Proclamation of Indonesian Independence 5) To know the Kasikan village was irrigated by Tapung Kiri River 6) To see the different sides of the Economic and Social Life in the Kasikan village community which was included in Tapung Kiri River flow. In this study using the methods of History (Historical Research) by study and explore values, facts to understand the past. The finding of pass material is using for the present even for the future. This research was conducted in the village of Kasikan, Tapung Hulu sub-district, Kampar. The results showed that the region of Tapung is located upstream of Siak River (Jantan River), Tapung also divided into two region, namely the Regionof Tapung Kanan and Tapung Kiri.Keywords: Kingdom of Siak, Tapung.